Comportamiento agronómico de cinco especies forestales del banco de germoplasma de la parte noroccidental de la provincia de Cotopaxi en el campo experimental La Playita de la Universidad Técnica Cotopaxi extensión La Maná. año 2014 - Pazmiño Herrera, Wilman Edmundo (2015)
This research was based on the Agronomic Performance of five forest species studied in field experimental La Playita of Technical University of Cotopaxi extension La Maná 2014 species were: Balsa (Heliocarpusamericanus), Mahogany (Swieteniamacrophylla), Laurel (Laurusnobilis L.), Cedar (Cedrelaodorata), Chiparo (Zygialongifolia) as general objective was to evaluate the agronomic performance of the five forest species it was product how specific objectives that were completely random (DCA) with five treatments, five replications and five plants as experimental unit, as variables of study was evaluated at days germination, the results were treatments the Balsa with 10 days, the longest value in the treatment Cedar with 11 days in the variable was obtained from transplant (Repique)....